Digital interactive module based on team games tournament to develop collaboration and student’s critical thinking skills on respiratory system material - Nada Thahira; Ummi Nur Afinni Dwi Jayanti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Collaboration and critical thinking skills are part of the 21st-century skills that must be mastered and developed. Therefore, innovative teaching materials are needed to help develop students' critical thinking and collaboration skills. This development research aims to produce Team Games Tournament (TGT) based digital interactive modules that are valid, practical, and effective for students. The instruments used are needs analysis in the form of teacher interview guidelines and questionnaires for students, teaching material and material expert validation sheets, and practicality sheets. Then, the effectiveness sheet is in the form of a pretest post-test sheet. Based on the results of the data analysis, the teaching material validation obtained a score of 98.55%, the material validation results obtained a score of 96.73%, the teacher response questionnaire results obtained a score of 97.92%, and the student response questionnaire results obtained a score of 93.15%. The effectiveness assessment resulted in an average N-Gain score of 0.80 with a high category, and the results of student collaboration skills scored 91 with a very effective category. Therefore, the TGT-based digital interactive module is considered a feasible, practical, and effective learning tool, facilitating the development of students' collaboration and critical thinking skills. However, further development research can expand the material on biology learning that has not been covered in the development of this interactive digital module.Abstrak. Kemampuan kolaborasi dan berpikir kritis merupakan bagian dari keterampilan abad ke-21 yang perlu dikuasai dan dikembangkan. Oleh karena itu, diperlukan bahan ajar yang inovatif yang dapat membantu mengembangkan kemampuan berpikir kritis dan kolaborasi siswa. Penelitian pengembangan ini bertujuan untuk menghasilkan modul interaktif digital berbasis Team Games Tournament (TGT) yang layak, praktis dan efektif bagi siswa. Instrumen yang digunakan adalah analisis kebutuhan berupa pedoman wawancara guru dan angket untuk siswa, lembar validasi ahli bahan ajar dan materi, serta lembar kepraktisan. Kemudian lembar keefektifan berupa lembar pretest post test. Berdasarkan hasil analisis data, validasi bahan ajar memperoleh skor 98,55%, hasil validasi materi memperoleh skor 96,73%, hasil angket respon guru memperoleh skor 97,92%, dan hasil angket respon siswa memperoleh skor 93,15%. Penilaian keefektifan menghasilkan rata-rata skor N-Gain sebesar 0,80 dengan kategori tinggi, dan hasil kemampuan kolaborasi siswa memperoleh skor 91 dengan kategori sangat efektif. Oleh karena itu, dapat disimpulkan bahwa modul interaktif digital berbasis TGT dinilai sebagai perangkat pembelajaran yang layak, praktis dan efektif, memfasilitasi pengembangan keterampilan kolaborasi dan berpikir kritis siswa. Namun demikian untuk penelitian pengembangan selanjutnya dapat memperluas materi pada pembelajaran biologi yang belum tercakup dalam pengembangan modul digital interaktif ini.